Factors Affecting an Individual's Future Labour Market Status - van der Merwe, Michelle (My University, 2016)
This article examines the ways in which someone’s characteristics and circumstances in one year affect their probability of being in a particular labour market state in the next year. People are more likely to be employed next year if they are currently employed and have tertiary qualifications. In contrast, they are more likely to be unemployed or outside the labour force if they have a long-term health condition, have not completed high school or are a migrant from a non-English-speaking background. Additionally, the article considers the changing importance of determinants over time, noting the role that changes in individual and household preferences as well as broader macroeconomic conditions are likely to have played.
RBA Bulletin
Bulletin
Keywords: Finance; Income, wealth and finances; Finance; Income, wealth and finance